Coupled Fixed Point Theorems for Nonlinear Contractions in Partial Metric Spaces - Sharifa Al-Sharif; Mohammad Al-Khaleel; Mona Khandaqji (International Journal of Mathematics and Mathematical Sciences)
We establish some results on the existence and uniqueness of coupled fixed point involving nonlinear contractive conditions in complete-ordered partial metric spaces.